2023
DOI: 10.3390/biom13020331
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Sex-Dependent Effects of Fingolimod Treatment in a Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common cause of dementia. Fingolimod has previously shown beneficial effects in different animal models of AD. However, it has shown contradictory effects when it has been applied at early disease stages. Our objective was to evaluate fingolimod in two different treatment paradigms. To address this aim, we treated male and female APP-transgenic mice for 50 days, starting either before plaque deposition at 50 days of age (early) or at 125 days of age (late). To evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
7
1
Order By: Relevance
“…A recent study showed that the beneficial effect of FTY720 on AD pathology was limited to male mice, a limitation we did not observe with Ponesimod. 53 The authors suggested that FTY720 mainly affects the neuroinflammatory reaction to ongoing Aβ deposition. Therefore, we conclude that the activity of FTY720 is distinct from that of Ponesimod, which stimulates phagocytosis and therefore, preserves the neuroprotective function of activated microglia in AD, even after deposition of amyloid plaques.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the beneficial effect of FTY720 on AD pathology was limited to male mice, a limitation we did not observe with Ponesimod. 53 The authors suggested that FTY720 mainly affects the neuroinflammatory reaction to ongoing Aβ deposition. Therefore, we conclude that the activity of FTY720 is distinct from that of Ponesimod, which stimulates phagocytosis and therefore, preserves the neuroprotective function of activated microglia in AD, even after deposition of amyloid plaques.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, H. perforatum extracts with different polarities were used as an oral treatment in APPtg mice. Appropriate treatment regimens and concentrations were pre-tested and, finally, an early treatment paradigm [39] was employed with a duration of 40 days from 40 days of age. After treatment, protein brain extracts were fractionated to evaluate the treatment's effects on the content of soluble and insoluble Aβ.…”
Section: Resultsmentioning
confidence: 99%
“…Animal model maintenance and husbandry were performed as previously described [39,59,60]. The individuals used in this study were housed at the Department of Comparative Medicine (section of the Radium Hospital) at the Oslo University Hospital (Oslo, Norway).…”
Section: Animal Models and Breeding Schemementioning
confidence: 99%
“…Fingolimod has emerged recently as a promising neuroprotective agent in a wide range of CNS diseases, including Alzheimer's disease (AD; reviewed, e.g., in Angelopoulou and Piperi 2019;Bascunana et al 2020;Pournajaf et al 2022). Importantly, fingolimod tackles those immunological and neuro-inflammatory processes that are triggered by amyloid-β and tau fibrillary tangle pathology (Aytan et al 2016;Baloni et al 2022;Bascunana et al 2023;Fagan et al 2022;Kartalou et al 2020).…”
Section: Fingolimod Receptors and Downstream Signaling Pathwaysmentioning
confidence: 99%